Integrated Curriculum: Concept, Characteristics and Consideration for Planning and Designing - Kuwar, Rajendra; Acharya, Nara Hari (ILAM इलम, 2024)
This article explores the conceptualization, characteristics, and framework for planning and designing an integrated curriculum with threefold objectives. The first is to examine the conceptual underpinnings of curriculum integration, emphasizing interconnectedness between subject areas and cross-disciplinary understanding; the second is to outline key characteristics of an integrated curriculum, including holistic learning, differentiated activities, balanced instruction, varied learning modes, critical and creative thinking, authentic assessment, and meaningful whole learning; and the third is to provide a comprehensive framework for effectively implementing an integrated curriculum. The review of the literature by different scholars is the main source of the data to address considerations for planning and designing an integrated curriculum, such as assessing learners, the school community, and context; identifying central themes; selecting and organising themes; sequencing; aligning with standards and objectives; selecting instructional strategies; developing authentic assessments; providing teacher professional development; involving stakeholders in participation and support; and developing instructional materials and resources. The careful planning and designing of the frameworks, along with the development of conceptual understanding and critical thinking skills in students to prepare for complexities of the 21st century, are the main parameters of the successful implementation of an integrated curriculum.